2016
DOI: 10.1149/2.1071606jes
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Slurry pH on the Expansion/Contraction Behavior of Silicon/Carbon/Carboxymethylcellulose Electrodes for Li-Ion Batteries

Abstract: Electrochemical dilatometry experiments were performed on silicon/carbon/carboxymethylcellulose (Si/C/CMC) composite electrodes prepared with pH7 and buffered pH3 slurries. It was shown that the pH3 electrode better accommodates the severe volume change of the micrometric Si particles, inducing a much better capacity retention with cycling (70% after 10 cycles compared to only 6% for the pH7 electrode). During the first discharge (lithiation), a maximum electrode thickness expansion of ∼170% was observed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…This is unfavorable, especially when considering that the volume expansion of Si particles is accommodated to some extent by the electrode’s porosity. 29…”
Section: Resultsmentioning
confidence: 99%
“…This is unfavorable, especially when considering that the volume expansion of Si particles is accommodated to some extent by the electrode’s porosity. 29…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Among the various binder materials to be considered for Si-based high capacity anode materials, poly (amide-imide) (PAI) shows some promising behavior as a binder for Si-based electrodes because of its high mechanical strength by secondary interaction from polyimide and hydrogen bonding from amide group in polyamide. [22][23][24][25][26][27][28] Among the various binder materials to be considered for Si-based high capacity anode materials, poly (amide-imide) (PAI) shows some promising behavior as a binder for Si-based electrodes because of its high mechanical strength by secondary interaction from polyimide and hydrogen bonding from amide group in polyamide.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al reported that simple heat treatment can further improve the cycle performance of Si-alloy electrode adopting PAI binder. To the best of our knowledge, although in situ dilatometric studies on the Si-based electrode using other binder materials such as carboxymethylcellulose (CMC), 27 Polyimide (PI), 25 PVDF 26 are reported, there are few reports on in-situ dilation monitoring of Si-based electrode employing PAI binder. 28 One can reasonably expect that thermally treated PAI binder, which have strong binding force, can suppress the volume expansion and reduce electrical contact loss of electrode.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations